Extended Reality 기반 고령자 대상 인지 · 운동 기능 훈련 워크벤치 개발 및 콘텐츠 설계 제안 - 김태홍(Taehong Kim); 김중일(Joong Il Kim); 서정우(Jeong-Woo Seo); 도준형(Jun-Hyeong Do) (한국정보통신학회논문지, 2022)
One of the most negative social changes of the last decade is population aging which leads to 19 times more patients with Mild Cognitive Disorder(MCI). It is well established that MCI is the most important state that can prevent dementia with early diagnosis and intervention. However, the social security system for patients with dementia is not working properly due to the coronavirus pandemic and the limited human power. This article proposes a form of workbench and design principles for dementia training programs of extended reality devices. and the findings in this study provide a guide for considering the cognitive and physical and social functions of patients.